Medical Takaful (Insurance) Reform: Models And Structures - Billah, M. M. (Universiti Sains Islam Malaysia, 2024)
Living with healthy life is among the prime natural concern of everyone regardless of one's status or background. A proper health–care requires money and today, it is one of the most expensive components of expenditure, which is not affordable to everyone thus, medical takaful (insurance) may be a solution. In view of creating a healthy society, several developing countries make the medical insurance compulsory. In the Kingdom of Saudi Arabia on the other hand, the health insurance has not been made mandatory yet on everyone living in the Kingdom, the native or the expatriate. The law of the Kingdom in general, is a Shari’ah (Islamic law) while its recognized insurance model is based on the cooperative (ta’awuni) principles (Al-Qur’an (5:2). In creating a healthier society by encouraging everyone to care about health, the medical takaful may be an effective step to be taken in to consideration thus, its reform is an emergence factor by allowing choices in package within the supreme law of the Kingdom. An attempt is thus made in this paper to analyze possible reformed models and structures of medical insurance appropriate for the Kingdom's environment. In establishing the idea, some experiences will be analyzed as a reference from the existing practices of the Kingdom of Saudi Arabia and also the Malaysian practices of medical takaful as the pioneer of the scheme.